Methods in Quaternary Ecology #4. Freshwater Sponges - Harrison, Federick (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1988)
Summary In recent years, there has been an increased awareness of the value of fossilized remains of freshwater sponges in Quaternary paleo-ecological reconstructions. Because the taxonomy and ecology of extant forms have been clarified, and because a well-defined fossil record exists that exhibits continuity with extant species, the stage is set for wide-spread utilization of freshwater sponge remains in Quaternary environmental reconstructions. This paper presents an introduction to the freshwater sponges, techniques for their utilization in Quaternary paleo-ecological studies, and summarizes some of the most recent work performed in North America.